2011
DOI: 10.1002/clen.201000259
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Removal through Biosorption and Bioaccumulation by Bacteria from Tannery Effluents Contaminated Soil

Abstract: Four bacterial isolates (two resistant and two sensitive to chromium) were isolated from soil contaminated with tannery effluents at Jajmau (Kanpur), India, and were identified by 16S rDNA gene sequencing as Stenotrophomonas maltophilia, Exiguobacterium sp., Pantoea sp., and Aeromonas sp. Biosorption of chromium by dried and living biomasses was determined in the resistant and sensitive isolates. The effect of pH, initial metal concentration, and contact time on biosorption was studied. At pH 2.5 the living bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Biosorption is a cutting-edge technology, which involves sorption of dissolved substances by a biosorbent which can significantly reduce the cost of chemical usage and pollution compared to the other traditional Cr(VI) removal processes 14 , 17 , 18 . Several investigations have been reported on metal binding efficiencies of various strains of bacteria, algae and fungi 4 , 14 , 19 26 . Among them, fungi are the best choice because of high cell wall material percentage and outstanding metal binding properties 2 , 8 , 14 , 23 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Biosorption is a cutting-edge technology, which involves sorption of dissolved substances by a biosorbent which can significantly reduce the cost of chemical usage and pollution compared to the other traditional Cr(VI) removal processes 14 , 17 , 18 . Several investigations have been reported on metal binding efficiencies of various strains of bacteria, algae and fungi 4 , 14 , 19 26 . Among them, fungi are the best choice because of high cell wall material percentage and outstanding metal binding properties 2 , 8 , 14 , 23 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have reported that materials with biological and natural origins, such as agricultural, banana peel, peel waste, and animal waste, are effective and usable in the removal of metals [9,[12][13][14][15][16]. Some sorbents such as seaweed (Gymnogongrus Torulosus) [17], leaf powder (Ficus religiosa) [18], and bacteria (Tannery Effluents Contaminated Soil) [19] were used for metal removal. Bones are composed of 30% organic compounds and 70% inorganics by weight [20].…”
Section: Introductionmentioning
confidence: 99%
“…Both the living and dried biomass of Exiguobacteriumsp. absorbed maximum amount of Cr(VI) from aqueous solution 64 . Furthermore indigenous chromium reducing bacterial strain, Ochrobactrumintermedium RB-2 was isolated from tannery waste samples and was examined for its potential to reduce Cr(VI) to Cr(III).…”
Section: Mechanism Of Bacterial Resistance To Cr(vi)mentioning
confidence: 99%